2013
DOI: 10.1186/1746-6148-9-14
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein, haptoglobin, serum amyloid A and pig major acute phase protein response in pigs simultaneously infected with H1N1 swine influenza virus and Pasteurella multocida

Abstract: BackgroundSwine influenza (SI) is an acute respiratory disease caused by swine influenza virus (SIV). Swine influenza is generally characterized by acute onset of fever and respiratory symptoms. The most frequent complications of influenza are secondary bacterial pneumonia. The objective of this work was to study the acute phase proteins (APP) responses after coinfection of piglets with H1N1 swine influenza virus (SwH1N1) and Pasteurella multocida (Pm) in order to identify whether the individual APP response c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 21 publications
2
31
1
2
Order By: Relevance
“…These results indicate that the measurement of APP such as SAA may prove valuable in assessing the severity of respiratory infection in pigs, and may be of supportive value in the clinical evaluation of animals and in the selection of more appropriate treatment. In agreement with the present results, the positive relationship between SAA and disease severity was also reported previously in pigs, humans, and other species (4,9,15,28,29).…”
Section: Discussionsupporting
confidence: 82%
“…These results indicate that the measurement of APP such as SAA may prove valuable in assessing the severity of respiratory infection in pigs, and may be of supportive value in the clinical evaluation of animals and in the selection of more appropriate treatment. In agreement with the present results, the positive relationship between SAA and disease severity was also reported previously in pigs, humans, and other species (4,9,15,28,29).…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that CRP and SAA are similar in terms of the stimuli for their production and the kinetics of their synthesis and bioavailability, while these are somewhat different for Hp. Heegaard et al (2011) andPomorska-Mól et al (2013) both found that CRP and SAA release was much faster and not as prolonged, compared to Hp in other species. Moreover, it has been found that some types of infectious or inflammatory stimuli stimulated CRP and SAA production, but did not have an effect on the serum concentration of Hp (Eckersall et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, in a study conducted on pigs, the concentration of acute phase proteins increased significantly from 48 to 72 h (Pomorska-Mol et al, 2013). However, Gomez-Laguna et al (2010) indicated an increase of acute phase proteins through the intranasal routes challenge by P. multocida infection in mice model within 36 h of post infection.…”
Section: Discussionmentioning
confidence: 99%